Fractal analysis as a useful predictor for determining osseointegration of dental implant? A retrospective study - Emrah Soylu; Aykağan Coşgunarslan; Selin Çelebi; Damla Soydan; Ahmet Emin Demirbaş; Osman Demir (SpringerOpen, 2021)
Abstract Purpose The present study aimed at evaluating the effectiveness of fractal analysis on determining the osseointegration of dental implants. Material and methods In a single center, retrospective clinical trial, patients with dental implants in the mandibular premolar/molar region, ASA I-II and < 65-year-old patients were included. Orthopantomograph (OPG) were taken before implant surgery (t0), within a week of surgery (t1), and 1 (t2) and 2 (t3) months after surgery, respectively. Three regions of interest (ROIs) from mesial, distal, and apical sites of the implants were chosen and fractal analysis (FA) was conducted with the box-counting algorithm using White and Rudolph's method. Results A total of 39 patients 19 women and 20 men, with a mean age of 52.2 years (52.3 and 52.1 years, respectively) were included. The mean, minimum and maximum values of mesial (roi1), distal (roi2), and apical (roi3) surfaces were compared. The fractal dimension (FD) values of t1 were significantly lower compared with t0 as they decreased during the first week. FD values gradually increased after the first week although never exceeded the FD values of t0. Also, difference between mean FD values of t0 and t3 were found statistically significant (p < 0.05). Discussion FA is a promising and noninvasive method to predict osseointegration of a dental implant based on dental radiographs, and it can help shorten the total treatment time.